KUR’ÂN’IN METİNLEŞME SÜRECİ BAĞLAMINDA ORYANTALİSTTİK GÖRÜŞLERİN KARŞILAŞTIRILMASI - Naif YAŞAR (Fırat University, 2019)
Jews and Christians have been interested in the Islam Prophet (pbuh) and the Qur’an from the very beginning of the Islamic history. They started to write critics on the Qur’an from the second century of hijra and on. The Western world’s struggle against Islam ranged parallel to the spreading of Islam from the Far East to the Middle Europa. In order to struggle against Muslims in a better way, the Westerners have started to examine the East and make close acquaintance with it both physically and spiritually and tried to manage it from the seventeenth century and on. Thence, a group who were called “orientalist” and who have devoted their lives to the oriental studies came out. Discovering that the Qur’an is the most important source for Muslims both for their everyday life and intellectual life, the orientalists have come up with numerious sceptical claims and hyphotheses about the authenticity of the Qur’an in order to put the Muslim communities into a suitable shape for the westerners’ governments. But because they couldn’t set forth scientifical proofs for these hyphotheses about the Qur’an, they were not able to refute the Muslims’ thoughts about the authenticity of the Qur’an and so the oreintalists have failed to reconstruct the textualization history of the Qur’an. In this article we will mainly rely on their claims about the textualization process of the Qur’an and would compare their pros and cons hypotheses related to the subject matter. Meanwhile we will touch on the orientalism history in order to remind its characteristical aspects and historical background.